Synergy effect of polyaspartic acid and D-phenylalanine on corrosion inhibition caused by Desulfovibrio vulgaris - Pang, Bo; Li, Hongyi; Ding, Chengcheng; Song, Chao; Wang, Shuguang (Frontiers in Materials, 2024)
Microbiologically influenced corrosion (MIC) poses a threat to various fields, particularly in piping and cooling water systems. As a green corrosion inhibitor, polyaspartic acid (PASP) faces challenges in achieving the intended corrosion inhibition against MIC due to biofilm. Therefore, mitigating biofilm might be the key to improving the corrosion inhibition of PASP. D-Phenylalanine (D-Phe) was selected as an enhancer to promote the inhibition of PASP on MIC caused by Desulfovibrio vulgaris due to its potential role in biofilm formation in this work. The joint application of PASP and D-Phe reduced the corrosion rate by 76.54% and obviously decreased the depth of corrosion pits with the maximum depth at 0.95 µm. Also, fewer cells adhered to the coupon surface due to the combined action of PASP and D-Phe, leading to thin and loose biofilm. Besides, both cathodic and anodic reactions were retarded with PASP and D-Phe, resulting in a low corrosion current at 0.530×10 -7 A/cm 2 . The primary synergy mechanism is that D-Phe promoted the formation of PASP protective film via decreasing bacterial adhesion and thus inhibited electrochemical reaction and electron utilization of cells from metal surface. This study introduces a novel strategy to augment the effectiveness of PASP in inhibiting MIC.